Chemically reactive squeezed flow of magnetized Al2O3 - PAO nanolubricant over a sensor surface with thermophoretic particle deposition - Riaz, Muhammad; Khan, Nargis; Hashmi, M. S.; Salleh, Zabidin; İnç, Mustafa (Elsevier, 2024)
The exceptional lubricating properties and stability of Al2O3 - PAO nanolubricant make it a suitable option for many industries such as automotive, aerospace, renewable energy, and medical. This study aims to examine the squeezed flow of magnetized nanolubricant (Al2O3 - PAO) across a sensor surface alongwith the fascinating impacts of nonlinear heat generation, thermal radiation and thermophoretic particle deposition (TPD). Heat transfer phenomenon is further observed in the presence of viscous dissipation and Joule heating. In order to make this investigation more convenient, the thermal conductivity is assumed to be variable. The introduction of nanolubricant Al2O3 - PAO as a flow fluid over a sensor surface and the use of Patel model of thermal conductivity are novel features of this work. The mass transfer phenomenon is further supported by applying chemical reaction of higher order. With the introduction of apposite similarity transformations, the governing PDEs have been modified to ODEs. We have treated the resulting ODEs numerically by using MATLAB built-in bvp-4c solver. It is perceived that the improving values of solid volume fraction and magnetic parameter play a substantial role in enhancing velocity and temperature of the nanolubricant Al2O3 - PAO, while squeezed flow index causes a decline in velocity as well as in temperature of the nanolubricant. The concentration profile declines for chemical reaction parameter and thermophoretic parameter, whereas increasing order of chemical reaction tends to enhance the concentration profile.
Keywords: Squeezed flow; Nonlinear heat generation; Chemical reaction; Sensor surface; Thermophoretic particle deposition; Bvp-4c solver